Analysis of Social Return on Investment (SROI) in Gen UNAIR + Program With The Theme an Inspiring Class: The Past and Younger Generation Meet in Class - Yudhistira Satria Pamungkas; Dipo Satria Alam; Roben Saosa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Many life lesson stories can be obtained from them in the form of wisdom that they have gone through starting from the entry of technology until today's era. This wisdom can later be used as a basis for the millennial generation and so on to live side by side with technological sophistication. So that they can purposefully utilize existing technology. Along with the SDGs by contributing to the achievement of SDG number 4, namely Quality Education, ensuring equal access to quality education that is prosperous and inclusive. So, our CSV strategy is the first step in supporting the 2030 agents for Sustainable Development. The research method used is quantitative causality by identifying stakeholders, social impact indicators, data collection, monetarization value and then calculating the SROI value. The result was obtained a ratio of 28.38 which means that every Rp1 invested in the GEN UNAIR + program, will generate social returns of Rp28.38 rupiah. The value of this SROI is relatively high and produces relatively high returns.